Neuroprotective effects of pterostilbene against isoflurane-induced apoptosis through regulating the JNK and PI3K/Akt pathway in neonatal rats (Bangladesh Journal of Pharmacology, 2015)
Increasing numbers of children undergo surgery and are exposed to anesthesia that raises concerns regarding the safety of frequently employed anesthetics. Isoflurane, often used in pediatric anesthesia, has been reported to cause neurodegeneration in animal models. The study investigates the effectiveness of pterostilbene on neurodegeneration caused by isoflurane. Separate groups of neonatal mice were administered with pterostilbene at 10, 20 or 40 mg/kg from post natal day 1 (P1) to P15. On P7, rats received isoflurane at 0.75% for 6 hours. Control rats received no anesthesia or pterostilbene. Neuroapoptosis following isoflurane exposure were markedly reduced by pterostilbene , further pterostilbene  down-regulated the expre-ssions of caspase-3, Bad, phospho-JNK and phospho-c-Jun and as well improved the expressions of Bcl-xL, JNK, phospho-Bad and phospho-Akt. Pterostilbene enhanced the performance of rats in Morris water maze tests. The observations suggest that pterostilbene was able to effectively reduce isoflurane-induced neurodegeneration.